The Freedom of Lights : Edmond Jabès and Jewish Philosophy of Modernity. - Poniatowska, Patrycja. (Studies in Jewish History and Memory Series, 2019)
The book offers a comprehensive philosophical reconstruction of the work of Edmond Jabès─a Jewish-French poet, modern Kabbalist and thinker. It is a starting point for an enquiry into the nature of the encounter between Judaism and modern philosophy. Philosophically, Judaism becomes a re-constructed tradition: a field played with by modern forces.